SYIAH DAN SUNNI DALAM PERSPEKTIF PEMIKIRAN ISLAM - Abidin, Zainal (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Shiite and Sunnite are two great Muslim groups emerging after the Prophetâs death. Shiite was considered a minor Muslim group who claimed that it was Ali ibn Abi Thalib who was eligible to a caliph (imam) after the Prophetâs death. Its reason was that Ali ibn Abi Thalib was the closet family of all Prophetâs companions. However, as a mayor Muslim group, Suniite claimed that all Prophetâs companions were eligible to a chaliph since the Prophet left no message to any of his copmpanions on who would be a chaliph after his death. It was this fact that aroused dispute on the chaliphate between the two Muslim groups.Â Kata Kunci: Syiâah, Sunni, imamah, khilafah